2015
DOI: 10.1088/1009-0630/17/9/06
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Nonequilibrium 2D Modeling of Nitrogen Inductively Coupled Plasma Flow

Abstract: Two-dimensional (2D) numerical simulations of thermochemical nonequilibrium inductively coupled plasma (ICP) flows inside a 10-kW inductively coupled plasma wind tunnel (ICPWT) were carried out with nitrogen as the working gas. Compressible axisymmetric Navier-Stokes (N-S) equations coupled with magnetic vector potential equations were solved. A fourtemperature model including an improved electron-vibration relaxation time was used to model the internal energy exchange between electron and heavy particles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…One investigation of nitrogen plasma flows was performed by Minghao et al [38] The results of this investigation indicated that the simulated temperature was 1500 K higher than experimental measurements at the center axis of the torch at a location of x=99 mm. Minghoa found that the plasma flow tended to be in thermal nonequilibrium in the discharge region of the torch, whilst the plasma approximated local thermal equilibrium in the vacuum chamber.…”
Section: Modelling Of Non-local Thermodynamic Equilibriummentioning
confidence: 80%
See 1 more Smart Citation
“…One investigation of nitrogen plasma flows was performed by Minghao et al [38] The results of this investigation indicated that the simulated temperature was 1500 K higher than experimental measurements at the center axis of the torch at a location of x=99 mm. Minghoa found that the plasma flow tended to be in thermal nonequilibrium in the discharge region of the torch, whilst the plasma approximated local thermal equilibrium in the vacuum chamber.…”
Section: Modelling Of Non-local Thermodynamic Equilibriummentioning
confidence: 80%
“…It is clear that a significant increase in temperature occurs after the gas passes into the coil region. Minghoa's nonequilibrium nitrogen experiment: (a) Model Geometry Source:Figure 9from Minghoa[38], (b) Comparison of simulated and measured temperatures along axis of ICPWT. Source:Figure 12from Minghoa[38]…”
mentioning
confidence: 99%